Pembinaan Mini First aid dan Sosialisasi Wajib Pajak pada Pelaku Pariwisata di Badung Bali - Putu, Austin Widyasari; Ni Putu, Indah Kusumadewi Riandra (Jurnal Abdi Mahosada, 2024)
The recovery of tourism in Bali has a positive impact on tourism actors, although not 100% like before the Covid-19 pandemic. Tourism actors as partners are engaged in the industry of providing accommodation and travel services that often find conditions of small accidents experienced. This makes partners feel the need to gain knowledge about First aid so that they can provide first aid in the event of an accident. In addition, partners also feel that they lack a correct understanding of the obligations of reporting and paying taxes, especially as tourism actors. The purpose of this PKM is to increase partners' knowledge and skills regarding fist aid and taxpayers. The solutions provided are counselling on fist aid and taxpayers and training on first aid cases. The results of this PKM obtained an increase in partner knowledge and skills which were evaluated verbally. It can be concluded, the provision of first aid and taxpayer socialisation needs to be carried out regularly on tourism actors to support the work of partners.